Pigeons and choughs, a usual resource for the Neanderthals in Gibraltar. (9th November 2016) - Blasco, Ruth; Rosell, Jordi; Rufà, Anna; Sánchez Marco, Antonio; Finlayson, Clive
Abstract: An ecological perspective is essential to our understanding of variations in the faunal communities and their relationships with human groups, as well as the foraging strategies that hominids practised in Pleistocene environments. Using the Middle Palaeolithic avifauna, the ecological quality of the Strait of Gibraltar shows a complex scenario in which cliff-dwelling species represented one of the most important and abundant taxa. Pigeons ( Columba ) are a species that favour rocky habitats, typically nesting on cliff ledges and at the entrances to large caves, while corvids are forest birds and only a few Palaearctic species, including colonial ones such as choughs ( Pyrrhocorax ), can also breed on rocky outcrops or cliffs. At Gorham's Cave, Gibraltar, the Neanderthals exploited pigeons and choughs for a period of more than 40 ka, with the earliest evidence dating from at least 67 ka. We show that such exploitation was not occasional, having found repeated evidence of the practice in different layers within the cave. The Gibraltar sites seem to provide ideal conditions for broadening the spectrum of prey during MIS 3. The high diversity of avian species identified in the faunal assemblages could be related to the location of the caves, which enables the exploitation of coastal and rocky habitats. This fact seems to point to the unique circumstances and foraging opportunities at this particular locality, where the available prey and environmental conditions seem to be influencing, among other factors such as site functionality and socio-cultural variables, the Neanderthal diet.